Adición de hongo Agaricus Bisporus como sustituto de la carne de cerdo en la calidad del chorizo ahumado tipo I - Muñoz Solórzano, Kimberly Nicole (2022)
The purpose of the research was to evaluate the addition of the fungus Agaricus bisporus in the quality of type I smoked chorizo in proportions of 20%, 30%, 40%, 50% and 60%. A one-factor design was applied in DCA with three repetitions, with 15 experimental units, the experimental unit consisted of 5 kg. The physicochemical parameters (pH, acidity, fat and protein) were evaluated; Sensory (color, odor, and flavor) and texture profile (hardness, adhesiveness, elasticity, cohesiveness, and chewiness). The results showed that the variables VpH and acidity are highly significant P_value (>0.05), while for protein and fat the assumptions of Anova were not met, resulting in non-significant P_value (<0.05), therefore, you should proceed to perform a Shapiro Wilk test. In the sensory evaluation the best treatment was considered T1 (20% addition of fungus) and within the analysis of the texture profile the parameters of hardness 6, 78 N and adhesiveness - 0.56 Kg m2 / s2. The results of the investigation determined that the T1 treatment (20% addition of fungus) complies with the technical standard for meat and meat products NTE INEN (1338: 2012), which is why it is considered the best treatment.